2010
DOI: 10.1111/j.1467-8330.2010.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Space as Emancipation: Meditations on Anarchism, Radical Democracy, Neoliberalism and Violence

Abstract: In establishing an anarchic framework for understanding public space as a vision for radical democracy, this article proceeds as a theoretical inquiry into how an agonistic public space might become the basis of emancipation. Public space is presented as an opportunity to move beyond the technocratic elitism that often characterizes both civil societies and the neoliberal approach to development, and is further recognized as the battlefield on which the conflicting interests of the world's rich and poor are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 80 publications
0
88
0
5
Order By: Relevance
“…Nevertheless, future research could add to the already existing literature on democracy and neoliberalism (Leys, 2003;Springer, 2011;Swyngedouw, 2015) consideration of the extent to which democracy in general, and representative democracy in particular, remains an oxymoron under neoliberalism. In addition to rejecting the main basis of democracy, the sovereign people, neoliberalism threatens political representation as such.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, future research could add to the already existing literature on democracy and neoliberalism (Leys, 2003;Springer, 2011;Swyngedouw, 2015) consideration of the extent to which democracy in general, and representative democracy in particular, remains an oxymoron under neoliberalism. In addition to rejecting the main basis of democracy, the sovereign people, neoliberalism threatens political representation as such.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, some of the analyses that have searched for continuities with other recent mass mobilizations have revealed that various partial mobilizations stemmed from certain injustice frames and, that they also evoked Gezi resistance.This approach involves describing the demonstrations' subjects concretely. For instance, workers, environmentalist organizations, supporters of soccer teams, secular, urban and/or middle class women, and Alawites are some of the agents referring to certain injustice frames that emerged during JDP's governing period between 2011(Dogan 2014. Any frame, indicating both a certain antagonism and subjectivity,constitutes a set of agencies and identities acting in protests.…”
Section: Features Symbols and Subjectsmentioning
confidence: 99%
“…(Kristeva, 2006) It is space in which what is legitimate, and what is not, is shifting, debated and contested (Arendt, 1964a). Worldliness is contestation of repressive power and rejection of coercive authority [Springer, 2011;Jun, (2010), p.51]. Contestation is judgement of, for example, the authority of bureaucracy, which is problematic precisely because it is so abstract, as shown above.…”
Section: Space and Ephemeral Acts Of Autonomy -Creative Spacementioning
confidence: 99%
“…Thus, it is a collective process of making social space in which the subject comes to be and act, and, in turn, produces space. This constellation needs the physical space for people to come together, collaborate and appear as legitimate claimants (Springer, 2011). Such recognition might lead to a different outcome than violence of arrest, physical violence and deportation back into the Saharan desert (Collyer, 2010), although it might just as likely lead to no more than a moment's hesitation.…”
Section: Social Embryos Of Political Existence?mentioning
confidence: 99%